1993
DOI: 10.1111/j.1432-1033.1993.tb19894.x
|View full text |Cite
|
Sign up to set email alerts
|

The cooperative binding of phenylalanine to phenylalanine 4‐monooxygenase studied by 1H‐NMR paramagnetic relaxation

Abstract: The effect of the paramagnetic high-spin Fe(II1) ion in phenylalanine 4-monooxygenase (phenylalanine hydroxylase, EC 1.14.16.1) on the water proton longitudinal relaxation rate has been used to study the environment of the iron center. The relaxation rate was measured as a function of the concentration of enzyme, substrate (phenylalanine), inhibitor (noradrenaline) and activator (lysolecithin), asrwell as of the temperature (1 8 -40 "C) and the external magnetic field strength (100 -600 MHz). From the frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
37
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 50 publications
2
37
0
Order By: Relevance
“…During the past few years the mechanism of activation has been the subject of intense biochemical and spectroscopic studies, which have showed that activation of PheOH by the substrate is highly cooperative and always accompanied by alterations in the tertiary structure, but the nature of the conformational change has not been ascertained yet. Substrate activation has been proposed to involve cooperativity among all four subunits of the tetramer (33,34) and radiation target analysis has shown that activation of PheOH results in modification of the monomer structure and promotes stronger association at the dimer interface (35). These results are further supported by evidence of increase in volume of the tetrameric protein (30), and by a shift of the dimer 7 tetramer equilibrium toward the tetrameric form (31) upon binding of L-phenylalanine.…”
Section: Discussionmentioning
confidence: 96%
“…During the past few years the mechanism of activation has been the subject of intense biochemical and spectroscopic studies, which have showed that activation of PheOH by the substrate is highly cooperative and always accompanied by alterations in the tertiary structure, but the nature of the conformational change has not been ascertained yet. Substrate activation has been proposed to involve cooperativity among all four subunits of the tetramer (33,34) and radiation target analysis has shown that activation of PheOH results in modification of the monomer structure and promotes stronger association at the dimer interface (35). These results are further supported by evidence of increase in volume of the tetrameric protein (30), and by a shift of the dimer 7 tetramer equilibrium toward the tetrameric form (31) upon binding of L-phenylalanine.…”
Section: Discussionmentioning
confidence: 96%
“…The tetrameric form of mammalian PAH displays homotropic cooperative binding of the substrate L-Phe, as observed by steady-state enzyme kinetics and equilibrium binding studies (2,8,28,29). The cooperativity has so far primarily been interpreted within the framework of the classical concerted two-state model of Monod et al (30), i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of rat PAH by L-Phe has been interpreted to result from a cooperative binding of the substrate either to a putative allosteric/regulatory site, which is distinct from the catalytic site (Phillips et al, 1984a;Shiman et al, 1990Shiman et al, , 1994Parniak, 1987), or to the active site near the iron (Martinez et al, 1990(Martinez et al, , 1993. The positive cooperativity of LPhe binding seems to reflect changes in the quaternary structure coupled to changes in the tertiary structure of the subunits, by which a form with low-affinity for L-Phe and low-activity (Tform) is converted to a form with high-affinity and high-activity (R-form) (Kaufman, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The activation by L-Phe has been found to result in concomitant conformational changes involving the tertiary and quaternary structure (Phillips et al, 1984b;Kappock et al, 1995), changing the tetramer -dimer equilibrium towards the tetrameric form both for rPAH (D@skeland et al, 1982;Parniak, 1987) and recombinant hPAH (Martinez et al, 1995). Moreover, L-Phe binding seems to induce the displacement of a water molecule which is coordinated to the iron in the resting, non-activated rat enzyme (Martinez et al, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation